Penggunaan Insulin Basal dalam Praktek Sehari-hari: Panduan Praktis untuk Dokter Umum - Dani Rosdiana (Jurnal Ilmu Kedokteran, 2014)
Prevalence of diabetes mellitus in Riau have reached 10,4 %, it’s higher than national pravelence. Hence, it’s needmore attention from physician. The important thing in managing DM is how to restrain controlled blood sugar level.The best parameter to evaluate controlled blood sugar level is level of HbA1c. Fasting blood glucose is one ofimportant component which determine HbA1c especially HbA1c more than 8,5%. There are some pharmacologyagent to decrease HbA1c level, and insulin is the most effective agent. Why physician needs insulin?It was caused by impairment of betha cell pancreas was directly propotional with DM progressiveness. Comprehensionand capability for using basal insulin are important to physician, not only for internist but also for general practinioner.As we know that general practinioner have a competency to manage DM without complication. Guidance for usingsimple and practical basal insulin is expected will facilitate physician to manage blood sugar level of DM patient.